Ibuprofen-Amino Acids Co-Crystal Screening Via Co-Grinding Methods - Muhamad Fitri, Othman; Norasikin, Jamburi; Nornizar, Anuar; Syarifah, Abd Rahim; Nurul Hazwani, Rohalim (EDP Sciences, 2016)
The importance of pharmaceutical co-crystals now has been recognized in order to improve the research and development in pharmaceutical industries. Low solubility of active pharmaceutical ingredient (API) has led to the growth of new pharmaceutical co-crystals formation as it enhances the physicochemical properties of the API. In this works, preparation of new co-crystal formation between ibuprofen (IBP) with selected amino acid compounds were performed by using dry grinding and liquid assisted grinding (LAG) techniques. Ibuprofen (IBP) was selected as the API meanwhile glycine (GLY), L-alanine (ALA) and L-proline (PRO) were selected as co-crystal former (CCF) agents. The products of IBP-co-former from grinding experiments for the formation of co-crystals were characterized and verified using X-Ray Powder Diffraction (XRPD), Differential Scanning Calorimetry (DSC) and Fourier Transform Infra-Red Spectroscopy (FTIR). The finding reveals that the IBP-PRO co-crystals have successfully formed. For IBP-PRO system, new crystalline peaks from XRPD were recorded at 2θ values of 4.374°, 5.436° and 10.944° from dry grinding technique and 4.41°, 5.436° and 10.962° for liquid assisted grinding (LAG) technique. A new melting point of 257.49 °C was discovered for IBP-ALA indicates the possibility of co-crystals formation. On the other hand, the analysis for IBP-GLY shows that no co-crystals formed in the system.